2012
DOI: 10.1016/j.tsf.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

ZrB2 thin films grown by high power impulse magnetron sputtering from a compound target

Abstract: ZrB 2 thin films were grown on Si by high power impulse magnetron sputtering (HiPIMS) from a compound target in an industrial deposition system. By keeping a constant average power while modifying the HiPIMS pulse repetition frequency, the pulse peak current and thereby the degree of ionisation was varied. The films were characterised using X-ray diffraction techniques, scanning electron microscopy, time-of-flight elastic recoil detection analysis, and four-point probe measurements. It was found that the compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 39 publications
8
28
0
1
Order By: Relevance
“…SEM analysis shows a columnar growth for ZrB2 on Si(100), see Figure 6 for (a) a film deposited at RT and a substrate bias of -80 V and (b) at 550 °C and a substrate bias of -80 V. This behavior is in agreement with the results obtained for DCMS sputtered films in the study of Samuelsson et al [7]. Furthermore, the surface of the deposited films is in general smooth, in particular for films deposited at RT and with a bias voltage > -40 V, which is in accord with the results from the HRTEM investigation.…”
Section: Microstructuresupporting
confidence: 89%
See 4 more Smart Citations
“…SEM analysis shows a columnar growth for ZrB2 on Si(100), see Figure 6 for (a) a film deposited at RT and a substrate bias of -80 V and (b) at 550 °C and a substrate bias of -80 V. This behavior is in agreement with the results obtained for DCMS sputtered films in the study of Samuelsson et al [7]. Furthermore, the surface of the deposited films is in general smooth, in particular for films deposited at RT and with a bias voltage > -40 V, which is in accord with the results from the HRTEM investigation.…”
Section: Microstructuresupporting
confidence: 89%
“…This result is in contrast to Mitterer et al who found that the B/Zr ratio increased with increasing deposition temperature [9]. However, the condition that a high bias favors a Zr-rich composition is in accord with previous studies, as re-sputtering of boron during growth of ZrB2 from a compound target have been proposed by Mitterer et al [9] and Samuelsson et al [7], using DCMS and high power impulse magnetron sputtering, respectively. It is likely that a preferential re-sputtering process at moderate bias voltage of -80 V, as applied in our experiments, is eased at elevated temperatures.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations